1990
DOI: 10.1161/01.cir.81.5.1594
|View full text |Cite
|
Sign up to set email alerts
|

Validation of [1-11C]acetate as a tracer for noninvasive assessment of oxidative metabolism with positron emission tomography in normal, ischemic, postischemic, and hyperemic canine myocardium.

Abstract: Extraction and clearance kinetics of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 25 publications
(3 reference statements)
3
70
1
Order By: Relevance
“…22 Myocardial sectors defined by the polar map were then transferred to the whole dynamic sequence, and time-activity curves were obtained. The early phase of 11 C acetate washout was fitted monoexponentially to obtain the constant k(mono) as a previously validated measure of oxidative metabolism, 15 expressed in another polar map. The average of k(mono) for the whole map was calculated to define global myocardial oxygen consumption.…”
Section: Petmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Myocardial sectors defined by the polar map were then transferred to the whole dynamic sequence, and time-activity curves were obtained. The early phase of 11 C acetate washout was fitted monoexponentially to obtain the constant k(mono) as a previously validated measure of oxidative metabolism, 15 expressed in another polar map. The average of k(mono) for the whole map was calculated to define global myocardial oxygen consumption.…”
Section: Petmentioning
confidence: 99%
“…Clearance kinetics of 11 C acetate were used to quantify tricarboxylic acid cycle flux, which is directly related to overall myocardial oxidative metabolism. 15 By a combination with noninvasive measures of cardiac function, a previously validated estimate of myocardial efficiency was derived. 13 Additionally, the norepinephrine analogue 11 C HED was used in transplant recipients to quantify presence and extent of sympathetic reinnervation.…”
mentioning
confidence: 99%
“…These results can for the large part be attributed to the following factors. First, based on previous investigations, 19 Methods 1 and 3 assume that release of 11 Clabelled metabolites, such as amino acids, TCA cycle intermediates and 11 CO 2 , during the initial myocardial uptake phase is minimal. However, it has been shown that, within the first 2 and 4 minutes, nearly 14% and 42% of radioactivity, respectively, can be ascribed to 11 C-labelled metabolites.…”
Section: Journal Of Nuclear Cardiologymentioning
confidence: 99%
“…Second, several studies have shown that myocardial extraction of [ 11 C]acetate is incomplete, decreasing with increasing myocardial perfusion. 8,9,19 Recent data suggest that the extraction fraction of [ 11 C]acetate ranges from 90% to 80% within the flow range of .5-1.0 mL/ minute/g. 8,9 Therefore, K 1 , being the product of flow and extraction fraction, will always be lower than MBF.…”
Section: Journal Of Nuclear Cardiologymentioning
confidence: 99%
“…In a canine model with coronary artery stenosis, for the normal myocardial territory, when a vasodilator (e.g., adenosine or dipyridamole) is applied, regional blood flow will increase without a significant change in MVO 2 (24). According to Eq.…”
Section: Theory Of the Measurement Of Mpr With Bold Imagingmentioning
confidence: 99%